MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN BUTIR SOAL BERMUTU MELALUI PROGRAM WORKSHOP DI SD KATOLIK 079 NANGARASONG, SIKKA NUSA TENGGARA TMUR - BALTASAR MILI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Research based on the phenomenon is still many teachers who have difficulty in planning and holding daily tests. In addition, teachers often do not realize that assessments made through daily tests are not in accordance with the learning objectives and the learning process. So a research was conducted on increasing the ability of teachers to compile daily test questions through workshops. The research method used is classroom action research with two cycles. The number of respondents studied was 13 teachers. In cycle 1 an average of 2.82 or 53.84% of teachers was met, then cycle 2 gained an average of 3.72 or 90%, fulfilling the criteria. These results indicate a significant increase in teacher competence in preparing daily test items through workshop activities